Capacity building model development to improve the professionalism of vocational school teachers in the field of mechanical engineering expertise - Alchalil, Alchalil; Siraj, Siraj; Nasrah, Sayni; Dahrum, Dahrum (Universitas Malikussaleh, 2021)
The initial study has found several fundamental problems related to the professionalism of vocational teachers. These problems are in the form of 1) unequal teachers in getting the opportunity to participate in competency improvement programs; 2) lack of awareness in conducting research; 2) lack of desire to write articles and teaching materials, and 3) low level of desire to design instructional media in the field of mechanical engineering expertise. The objectives of this study were to 1) test the efficiency and effectiveness of the capacity building model; 2) find the determinants of success in professional development, and 3) produce a model for professional development of vocational teachers in the field of mechanical engineering expertise through effective and efficient capacity building. This study uses the Research and Development method. The subjects in this study were teachers in the field of mechanical engineering expertise in Bireuen Regency, the principal, two education management experts, and two mechanical engineering vocational education experts. Data collection techniques used in this research are through observation, interviews, FGD, documentation and questionnaires. Based on the research results, it can be concluded that the teacher capacity building model can improve teacher professionalism. These activities are carried out through the formation of learning communities, virtual self-education, writing, critical development groups, peer assistance, teacher exchanges, further studies, congregational action research, conferences and seminars, and ongoing training.